Packaging material
Patent Information
- Application Number
- JP2023133676
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2043-08-18
AI Technical Summary
【0013】 本開示により、高い外観性と高いレトルト性能を兼ね備える包装材を提供することができる。
Smart Images

Figure 2025028704000001 
Figure 2025028704000002 
Figure 2025028704000003
Abstract
Description
[Technical field]
[0001] This disclosure relates to packaging, and more particularly to packaging for heat-sterilized foods. [Background technology]
[0002] Patent Document 1 discloses a packaging material that can be heat sterilized when storing food. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2021-066031 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, there has been an increasing demand for adhesives that contain reduced amounts of solvents, preferably no solvents, due to the strengthening of legal regulations, consideration of environmental conservation and safety, restrictions on the release of volatile organic compounds into the atmosphere, etc. The adhesive constituting the packaging material disclosed in Patent Document 1 is a solvent-free adhesive that does not contain organic solvents.
[0005] On the other hand, solventless reactive adhesives that combine polyol and polyisocyanate have the problem that the viscosity is easily increased during application because they do not contain a solvent, which reduces the smoothness of the applied surface and generates fine bubbles during lamination, resulting in poor appearance. In addition, urethane adhesives that combine polyol and polyisocyanate have the problem that the polyisocyanate reacts with water during aging to generate carbon dioxide gas (bubbles), resulting in poor appearance. In addition, because they are food packaging materials, they need to have retort resistance that can withstand heat sterilization treatment.
[0006] The present disclosure has been made in consideration of these problems, and aims to provide a packaging material that combines high appearance and high retort performance. [Means for solving the problem]
[0007] The packaging material according to the present disclosure is a packaging material for heat-sterilized foods, and comprises at least a transparent vapor deposition film layer, an adhesive layer, and a plastic film layer, in this order, the adhesive layer being a cured product of a solvent-free adhesive, the solvent-free adhesive comprising a polyol base agent (A) containing a polyester polyol, and a polyisocyanate curing agent (B) containing an aliphatic polyisocyanate, and after mixing the polyol base agent (A) and the polyisocyanate curing agent (B), the viscosity at 40°C after 12 hours at 40°C is 80 Pa s or less.
[0008] In addition, in the packaging material according to the present disclosure, the polyol base (A) may contain a first polyester polyol (a1), and the first polyester polyol (a1) may have structural units derived from a polybasic acid having an aromatic ring and / or a monofunctional carboxylic acid having an aromatic ring, and the structural units may account for 20 mol % or more in total based on the total amount of carboxy group components.
[0009] In the packaging material according to the present disclosure, the first polyester polyol (a1) may contain 0 to 30 mol % of a structural unit derived from a polyhydric alcohol having an alkylene oxide group, based on the total amount of hydroxyl group components.
[0010] In addition, in the packaging material according to the present disclosure, the polyol base (A) further contains a second polyester polyol (a2), and the second polyester polyol (a2) has structural units derived from a polybasic acid having an aromatic ring and / or a monofunctional carboxylic acid having an aromatic ring, and the structural units may be contained in a total amount of 10 mol % or less based on the total amount of carboxy group components.
[0011] In the packaging material according to the present disclosure, the second polyester polyol (a2) may contain 0 to 20 mol % of a structural unit derived from a polyhydric alcohol having an alkylene oxide group, based on the total amount of hydroxyl group components.
[0012] In the packaging material according to the present disclosure, the solvent-free adhesive may contain an inorganic filler. Effect of the Invention
[0013] The present disclosure makes it possible to provide a packaging material that combines excellent appearance and high retort performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The packaging material according to the present disclosure is a packaging material for heat-sterilized foods, and includes at least a transparent deposition film layer, an adhesive layer, and a plastic film layer in this order, the adhesive layer being a cured product of a solvent-free adhesive, the solvent-free adhesive including a polyol base agent (A) containing a polyester polyol and a polyisocyanate curing agent (B) containing an aliphatic polyisocyanate, and the viscosity at 40°C after 12 hours at 40°C is 80 Pa·s or less after mixing the polyol base agent (A) and the polyisocyanate curing agent (B). If the viscosity at 40°C after 12 hours at 40°C is 80 Pa·s or less after mixing, time for bubbles to escape from the adhesive during aging can be secured, and the amount of bubbles remaining after curing can be suppressed. By including a polyester polyol and an aliphatic polyisocyanate and satisfying the above viscosity, it is possible to achieve both high appearance and high retort performance. The viscosity can be measured using a cone-plate viscometer in accordance with JIS K7117-2, and is preferably 75 Pa·s or less.
[0015] <Adhesive layer> The adhesive layer according to the present disclosure is a cured product of a solvent-free adhesive. The solvent-free adhesive contains a polyol base agent (A) containing a polyester polyol and a polyisocyanate curing agent (B) containing an aliphatic polyisocyanate. The solvent-free adhesive may be a mixture of the polyol base agent (A) containing a polyester polyol and the polyisocyanate curing agent (B) containing an aliphatic polyisocyanate, or may be applied separately and cured.
[0016] (Polyol base (A)) The polyester polyol contained in the polyol base material (A) is a compound having a hydroxyl group and an ester bond, and has the ester bond as a repeating unit. Examples of such polyester polyols include polyester polyols obtained by reacting a carboxyl group component with a hydroxyl group component; polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone); The above-mentioned carboxyl group component includes polybasic acid, and may be used in combination with monofunctional carboxylic acid. Such carboxyl group components include, for example, monofunctional carboxylic acid having aromatic ring such as benzoic acid, phenylacetic acid, 3-phenylpropionic acid, etc.; polybasic acid having aromatic ring such as terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, phthalic anhydride, trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, naphthalic acid, naphthalic anhydride, etc.; aliphatic polybasic acid such as adipic acid, azelaic acid, sebacic acid, succinic acid, glutaric acid, dodecane carboxylic acid, fumaric acid, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, maleic anhydride, itaconic anhydride, etc.; alkyl esters thereof; or mixtures thereof. The above-mentioned hydroxyl group component includes polyhydric alcohols, and may be used in combination with monofunctional alcohols. Examples of such hydroxyl group components include polyhydric alcohols having alkylene oxide chains such as diethylene glycol, dipropylene glycol, triethylene glycol, dineopentyl glycol, polyoxyethylene glycol, polyoxypropylene glycol, polytetramethylene ether glycol, and polyether polyols; polyhydric alcohols not having alkylene oxide chains such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, trimethylolpropane, glycerin, 1,6-hexanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 3,3'-dimethylolheptane, and 1,9-nonanediol; or mixtures thereof. As the hydroxyl group component, polycarbonate polyol, polyolefin polyol, acrylic polyol, polyurethane polyol, or a mixture thereof may be used.
[0017] These polyester polyols may be acid-modified products in which a portion of the hydroxyl groups in the polyester polyol is acid-modified, or may be products in which carboxyl groups have been introduced by reacting with an acid anhydride, or may be products in which urethane bonds have been introduced by reacting with a diisocyanate. Examples of the acid anhydride include pyromellitic anhydride, mellitic anhydride, trimellitic anhydride, and trimellitic ester anhydride. Examples of the trimellitic ester anhydride include ethylene glycol bisanhydrotrimellitate and propylene glycol bisanhydrotrimellitate. Examples of the diisocyanate include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, hexamethylene diisocyanate, and hydrogenated diphenylmethane diisocyanate.
[0018] The polyol base agent (A) may contain one type of polyester polyol or multiple types of polyester polyols. As the multiple types of polyester polyols, for example, at least one of the polyester polyols is preferably a polyester polyol obtained by reacting a carboxyl group component containing a polybasic acid having an aromatic ring with a hydroxyl group component from the viewpoint of retort resistance. In addition, examples of the polyester polyols include polyester polyols in which the proportion of polybasic acid components having aromatic rings and monofunctional carboxylic acids having aromatic rings is 15% by mass or more based on the total amount of all carboxyl group components and all hydroxyl group components constituting the polyester polyol, and polyester polyols in which the proportion of polybasic acid components having aromatic rings and monofunctional carboxylic acids having aromatic rings is 10% by mass or less. By using such polyester polyols in combination, the retort resistance is improved, and further, the coating property is excellent due to low viscosity, and the appearance is improved.
[0019] The polyol base agent (A) may contain a first polyester polyol (a1). The first polyester polyol (a1) has a structural unit derived from a polybasic acid having an aromatic ring and / or a monofunctional carboxylic acid having an aromatic ring, and contains the structural units in a total amount of 20 mol% or more, more preferably 25 mol% or more, based on the total amount of carboxy group components. By using a polyester polyol containing the first polyester polyol (a1), it is possible to improve the retort resistance of the adhesive. The proportion of structural units derived from polybasic acids having aromatic rings and monofunctional carboxylic acids having aromatic rings based on the total amount of carboxy group components is preferably 80 mol % or less, more preferably 60 mol % or less, and even more preferably 50 mol % or less, from the viewpoint of expressing adhesive strength.
[0020] Furthermore, from the viewpoint of retort resistance, the first polyester polyol (a1) contains 0 to 30 mol %, more preferably 0 to 25 mol %, of structural units derived from a polyhydric alcohol having an alkylene oxide group based on the total amount of hydroxyl group components. From the viewpoint of wettability to the surface to be coated, the first polyester polyol (a1) contains 50 mol % or more and 85 mol % or less of structural units derived from a polyhydric alcohol having an alkyl side chain based on the total amount of hydroxyl group components. Examples of polyhydric alcohols having an alkyl side chain include 1,2-propanediol, 1,3-butanediol, neopentyl glycol, and 2-methyl-1,3-propanediol.
[0021] The number average molecular weight of the polyester polyol (a1) is preferably 500 or more and 3,000 or less, more preferably 2,000 or less, and even more preferably 1,500 or less, from the viewpoint of coatability. From the viewpoint of adhesive strength, the polyester polyol (a1) may be an acid-modified product in which a part of the hydroxyl groups is acid-modified by reacting with an acid anhydride, and preferably is a product in which a carboxyl group is introduced by reacting with an acid anhydride. On the other hand, from the viewpoint of suppressing the increase in viscosity after 12 hours at 40°C, the acid value of the polyester polyol (a1) is preferably 2 mgKOH / g or more, preferably 15 mgKOH / g or less, more preferably 10 mgKOH / g or less, and even more preferably 5 mgKOH / g or less. From the viewpoint of curing properties of the adhesive, the hydroxyl value of the polyester polyol (a1) is preferably 30 mgKOH / g or more, more preferably 50 mgKOH / g or more, and preferably 200 mgKOH / g or less, more preferably 150 mgKOH / g or less.
[0022] The polyol base agent (A) may further contain a second polyester polyol (a2). The second polyester polyol (a2) has structural units derived from a polybasic acid having an aromatic ring and / or a monofunctional carboxylic acid having an aromatic ring, and contains the structural units in a total amount of 10 mol% or less, more preferably 8 mol% or less, based on the total amount of carboxyl group components. By using a polyester polyol containing a second polyester polyol (a2) having a small amount of structural units derived from such aromatic rings, not only can the viscosity of the polyester polyol (a2) be reduced, but also the increase in the viscosity of the adhesive after blending can be suppressed, improving the appearance.
[0023] Furthermore, from the viewpoint of retort resistance, the second polyester polyol (a2) contains 0 to 20 mol %, more preferably 0 to 10 mol %, of structural units derived from a polyhydric alcohol having an alkylene oxide group based on the total amount of hydroxyl group components. In addition, from the viewpoint of wettability to the surface to be coated, the polyester polyol (a2) preferably contains structural units derived from a polyhydric alcohol having an alkyl group side chain in an amount of 80 mol % or more and 100 mol % or less, based on the total amount of hydroxyl group components.
[0024] The number average molecular weight of the polyester polyol (a2) is preferably 1,000 or more and 3,000 or less, from the viewpoint of decreasing the viscosity of the adhesive and improving the coatability. From the viewpoint of suppressing an increase in viscosity of the polyester polyol (a2) after 12 hours at 40° C., the acid value of the polyester polyol (a1) is preferably 5 mgKOH / g or less, more preferably 3 mgKOH / g or less. From the viewpoint of curing properties of the adhesive, the hydroxyl value of the polyester polyol (a2) is preferably 30 mgKOH / g or more, more preferably 40 mgKOH / g or more, and preferably 200 mgKOH / g or less, more preferably 150 mgKOH / g or less.
[0025] The polyol base material (A) may contain a polyol other than the polyester polyol, so long as the effect of the present invention is not impaired. Examples of such other polyols include polycarbonate polyols, polyether polyols, polyolefin polyols, acrylic polyols, silicone polyols, and fluorine-based polyols. They may be acid-modified products in which a part of the hydroxyl groups is modified with an acid, products in which a carboxyl group is introduced by reacting with an acid anhydride, or products in which a urethane bond is introduced by reacting with a diisocyanate.
[0026] (Polyisocyanate hardener (B)) The aliphatic polyisocyanate contained in the polyisocyanate curing agent (B) refers to a compound having two or more isocyanato groups, in which the isocyanato groups are not directly bonded to an aromatic ring.
[0027] Such aliphatic polyisocyanates include, but are not limited to, well-known aliphatic diisocyanates, alicyclic diisocyanates, or compounds derived from these diisocyanates. Examples of the aliphatic polyisocyanate that can be used in the present invention include aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, 2,6-diisocyanate methyl caproate, and m-xylylene diisocyanate; 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3,4-diisocyanate, 4,5-diisocyanate, 5,6-diisocyanate, 6,7-diisocyanate, 7,8-diisocyanate, 8,9-diisocyanate, 9,10-diisocyanate, 10,11-diisocyanate, 12,12-diisocyanate, 13,13-diisocyanate, 14,14-diisocyanate, 15,16-diisocyanate, 17,17-diisocyanate, 18,18-diisocyanate, 19,19-diisocyanate, 20,20-diisocyanate, 21,22-diisocyanate, 22,23-diisocyanate, 23,24-diisocyanate, 24,25-diisocyanate, 25,26-diisocyanate, 26,27-diisocyanate, 27,28-diisocyanate, 28,29-diisocyanate, 29,30-diisocyanate, 29,31-di -alicyclic diisocyanates such as isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methyl 2,4-cyclohexane diisocyanate, methyl 2,6-cyclohexane diisocyanate, 1,4-bis(isocyanatomethyl)cyclohexane, and 1,3-bis(isocyanatomethyl)cyclohexane; and polyisocyanates such as allophanate type, nurate type, biuret type, and adduct type derivatives derived from the above-mentioned aliphatic diisocyanates or alicyclic diisocyanates, or complexes thereof. In addition, as the aliphatic polyisocyanate, a polyisocyanate having a urethane bond, which is a reaction product of the above-mentioned aliphatic diisocyanate, alicyclic diisocyanate or derivative thereof with a hydroxyl group component, may be used. As the hydroxyl group component used in the reaction, monofunctional alcohols and polyhydric alcohols may be mentioned, and the compounds described in the above-mentioned section (Polyol base agent (A)) may be used. In addition, polyester polyols, polycarbonate polyols, polyolefin polyols, acrylic polyols, polyurethane polyols, etc. may also be used. The derivatives are preferably nurate type and adduct type derivatives, and more preferably adduct type derivatives. From the viewpoint of the appearance of the packaging material and retort performance, the aliphatic polyisocyanate is preferably an alicyclic diisocyanate, more preferably a derivative of 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate. The alicyclic diisocyanate has low reactivity with the polyol base and can suppress the increase in viscosity after 12 hours at 40°C.
[0028] The polyisocyanate curing agent (B) may contain a polyisocyanate other than the aliphatic polyisocyanate, as long as the effect of the present invention is not impaired. Examples of such other polyisocyanates include aromatic polyisocyanates such as diphenylmethane diisocyanate and tolylene diisocyanate, and modified products thereof.
[0029] (Other ingredients) The solventless adhesive according to the present disclosure may contain components other than the polyol base agent (A) and the polyisocyanate curing agent (B) in order to satisfy various required performance characteristics. Such components may be blended into either the polyol base agent (A) or the polyisocyanate curing agent (B), or may be blended when the polyol base agent (A) and the polyisocyanate curing agent (B) are mixed. Each of these components may be used alone, or two or more of them may be used in combination.
[0030] The solvent-free adhesive according to the present disclosure may contain an inorganic filler. Examples of inorganic fillers include aluminum oxide, aluminum silicate, aluminum hydroxide, alumina white, potassium sulfate, zinc oxide, zinc carbonate, magnesium aluminometasilicate, magnesium silicate, magnesium oxide, magnesium carbonate, magnesium hydroxide, barium titanate, barium sulfate, barium carbonate, calcium carbonate, calcium hydroxide, calcium oxide, calcium silicate, calcium sulfite, calcium sulfate, titanium oxide, silica, zeolite, activated carbon, kaolin, talc, rosewood clay, silica stone, mica, graphite, sericite, montmorillonite, sericite, sepiolite, bentonite, perlite, zeolite, wollastonite, fluorite, and dolomite. By blending such a filler into the solvent-free adhesive, the cohesive force of the solvent-free adhesive after application is improved, and the appearance is improved.
[0031] The solventless adhesive according to the present disclosure may contain a silane coupling agent, or a phosphorus oxygen acid or a derivative thereof for the purpose of improving adhesive strength or acid resistance, and the amount of the agent is preferably 0.01 to 5 mass %, more preferably 0.02 to 3 mass %, relative to the mass of the polyol base (A). Examples of silane coupling agents include aminosilanes such as γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethyldimethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane; epoxysilanes such as β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane; vinylsilanes such as vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, vinyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; hexamethyldisilazane, and γ-mercaptopropyltrimethoxysilane. The phosphorus oxyacid may be any acid having at least one free oxyacid, and examples thereof include phosphoric acids such as hypophosphorous acid, phosphorous acid, orthophosphoric acid, and hypophosphoric acid; and condensed phosphoric acids such as metaphosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, polyphosphoric acid, and ultraphosphoric acid. Derivatives of phosphorus oxyacids include those obtained by partially esterifying the above phosphorus oxyacids with alcohols while leaving at least one free oxyacid. Examples of the alcohols include aliphatic alcohols such as methanol, ethanol, ethylene glycol, and glycerin, and aromatic alcohols such as phenol, xylenol, hydroquinone, catechol, and phloroglucinol. The solventless adhesive of the present disclosure may contain additives such as fillers, softeners, antioxidants, stabilizers, adhesion promoters, leveling agents, defoamers, plasticizers, tackifier resins, fibers, usable time extenders, antioxidants, ultraviolet absorbers, hydrolysis inhibitors, antifungal agents, thickeners, plasticizers, colorants such as pigments, and fillers, as necessary.
[0032] In this way, the solventless adhesive according to the present disclosure has low viscosity and excellent coatability, resulting in good appearance and also high retort resistance.
[0033] The solvent-free adhesive according to the present disclosure is a transparent vapor deposition film, which will be described later. layer , and plastic film layer The packaging material according to the present disclosure is a packaging material in which the adhesive layer, which is the cured product, is bonded to a transparent vapor deposition film. layer , and plastic film layer It is sufficient that the insulating film has a structure in which the insulating film is disposed between the first and second layers, and may further have another layer. The method for producing the packaging material according to the present disclosure is not limited. For example, the method may be a method for producing the packaging material according to the present disclosure. layer After applying the product, a plastic film is placed on the applied surface. layer and then curing the adhesive. The application temperature may be, for example, 40 to 100° C., preferably 60 to 90° C., taking into consideration workability and the viscosity of the solventless adhesive under heating. The above temperatures are preferable from the viewpoints that elasticity can be imparted after application and slippage of winding can be prevented. The solventless adhesive may be cured at room temperature or under heating, for example, at a temperature of 20 to 60° C. The amount of the solvent-free adhesive to be applied can be appropriately selected depending on the type of film and the coating conditions, and is preferably 1.0 to 5.0 g / m 2 , more preferably 1.2 to 3.5 g / m 2 It is.
[0034] <Transparent vapor deposition film layer> The transparent deposition film layer according to the present disclosure includes a deposition product of a metal or metal oxide and a first substrate. Examples of the metal or metal oxide include aluminum oxide, silicon oxide, magnesium oxide, and tin oxide. In particular, from the viewpoint of the retort performance of the packaging material, the metal or metal oxide is preferably aluminum oxide or silicon oxide. The metal or metal oxide can be formed, for example, by vacuum film formation. In the vacuum film formation, a physical vapor deposition method or a chemical vapor deposition method can be used. Examples of the physical vapor deposition method include, but are not limited to, a vacuum deposition method, a sputtering method, and an ion plating method. Examples of the chemical vapor deposition method include, but are not limited to, a thermal CVD method, a plasma CVD method, and a photo CVD method. In addition, a gas barrier coating layer may be provided on the metal oxide layer for the purpose of improving the gas barrier property and protecting the inorganic oxide layer. Although not particularly limited, the gas barrier coating layer may contain a hydroxyl group-containing polymer compound, specifically, a heat-dried product of a composition containing at least one of a hydroxyl group-containing polymer compound and its hydrolysate, and at least one selected from the group consisting of a metal alkoxide, a silane coupling agent, and their hydrolysates. Examples of the first substrate include polyester resin films such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polylactic acid (PLA); polyolefin resin films such as polyethylene (PE) and polypropylene (PP); polystyrene resin films; polyamide resin films such as nylon (NY) 6 and poly-p-xylylene adipamide (MXD6 nylon); polycarbonate resin films; polyacrylonitrile resin films; and polyimide resin films. The thickness of the transparent vapor-deposited film layer is preferably 5 μm or more and 50 μm or less, and more preferably 10 μm or more and 30 μm or less.
[0035] <Plastic film layer> The plastic film layer according to the present disclosure includes a second substrate, such as polyester resin films, such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polylactic acid (PLA); polyolefin resin films, such as polyethylene (PE) and polypropylene (PP); polystyrene resin films; polyamide resin films, such as nylon (NY) 6 and poly-p-xylylene adipamide (MXD6 nylon); polycarbonate resin films; polyacrylonitrile resin films; and polyimide resin films. The thickness of the plastic film layer is preferably 5 μm or more and 100 μm or less, and more preferably 10 μm or more and 50 μm or less.
[0036] The transparent vapor-deposited film layer and the plastic film layer may be a single layer or a laminate having a plurality of layers laminated together.
[0037] The packaging material according to the present disclosure may further include an ink layer. The location of the ink layer is not limited, and the ink layer may be provided on the transparent deposition film layer or the plastic film layer, or may be in contact with the adhesive layer. The thickness of the ink layer is preferably 0.1 to 10 μm, more preferably 1 to 5 μm.
[0038] In this way, a packaging material having both excellent appearance and excellent retort performance can be provided. EXAMPLES
[0039] The present disclosure will be described in more detail below with reference to examples, but the following examples are not intended to limit the scope of the present disclosure. In the examples, "parts" means "parts by mass" and "%" means "% by mass". In the examples, the methods for measuring "viscosity", "number average molecular weight (Mn)", "hydroxyl value (OHV)", and "acid value (AV)" are as follows.
[0040] [Viscosity]: Measured using a cone plate viscometer CV-1S manufactured by Toa Kogyo Co., Ltd. The temperature during measurement was 40°C. [Number average molecular weight]: The number average molecular weight was calculated using polystyrene equivalents when a Shodex GPC LF-604 (Shodex) column was used and THF was used as the developing solvent on a GPC (Shodex, GPC-104) equipped with an RI detector. [Hydroxyl value]: Measured in accordance with JIS K1557-1. [Acid value]: Measured in accordance with JIS K0070.
[0041] <Synthesis of polyester polyol> (Synthesis Example 1) Polyester polyol (a1-1) 175 parts of isophthalic acid, 320 parts of adipic acid, 49 parts of benzoic acid, 76 parts of ethylene glycol, and 380 parts of neopentyl glycol were charged into a reaction vessel, and the mixture was heated to 150-240 ° C. while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.1 (mgKOH / g), the reaction temperature was set to 200 ° C., the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3 kPa or less for 30 minutes, and then cooled to 110 ° C. Then, 5.0 parts of trimellitic anhydride (TMA) was added and acid-modified at 110 ° C. to obtain a polyester polyol (a1-1) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 40 mol % based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 0 mol % based on the total amount of hydroxyl group components. The number average molecular weight was 750, the acid value was 3.6 mgKOH / g, and the hydroxyl value was 104 mgKOH / g.
[0042] (Synthesis Example 2) Polyester polyol (a1-2) 274 parts of isophthalic acid, 447 parts of adipic acid, 94.9 parts of ethylene glycol, and 478 parts of neopentyl glycol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.2 (mgKOH / g), the reaction temperature was increased to 200°C, the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3 kPa or less for 30 minutes, and then cooled to 110°C. Then, 7.0 parts of trimellitic anhydride was added and acid-modified at 110°C to obtain a polyester polyol (a1-2) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 35 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 0 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 750, the acid value was 3.8 mgKOH / g, and the hydroxyl value was 104 mgKOH / g.
[0043] (Synthesis Example 3) Polyester polyol (a1-3) 100 parts of isophthalic acid, 88 parts of adipic acid, 24 parts of ethylene glycol, and 125 parts of diethylene glycol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.0 (mgKOH / g), the reaction temperature was increased to 200°C, and the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3 kPa or less for 30 minutes, and then cooled to 110°C. Then, 2.0 parts of trimellitic anhydride was added and acid-modified at 110°C to obtain a polyester polyol (a1-3) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 50 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 75 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 1,600, the acid value was 3.5 mgKOH / g, and the hydroxyl value was 67 mgKOH / g.
[0044] (Synthesis Example 4) Polyester polyol (a1-4) 100 parts of isophthalic acid, 88 parts of adipic acid, 72 parts of ethylene glycol, and 42 parts of diethylene glycol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.0 (mgKOH / g), the reaction temperature was increased to 200°C, and the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3 kPa or less for 30 minutes, and then cooled to 110°C. Then, 2.0 parts of trimellitic anhydride was added and acid-modified at 110°C to obtain a polyester polyol (a1-4) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 50 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide chains were 25 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 1,600, the acid value was 3.4 mgKOH / g, and the hydroxyl value was 67 mgKOH / g.
[0045] (Synthesis Example 5) Polyester polyol (a1-5) 157 parts of isophthalic acid, 550 parts of adipic acid, 94.9 parts of ethylene glycol, and 478 parts of neopentyl glycol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.2 (mgKOH / g), the reaction temperature was increased to 200°C, the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3 kPa or less for 30 minutes, and then cooled to 110°C. Then, 7.0 parts of trimellitic anhydride was added and acid-modified at 110°C to obtain a polyester polyol (a1-5) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 20 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 0 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 750, the acid value was 3.8 mgKOH / g, and the hydroxyl value was 104 mgKOH / g.
[0046] (Synthesis Example 6) Polyester polyol (a2-1) 100 parts of adipic acid and 90 parts of diethylene glycol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.0 (mgKOH / g), the reaction temperature was increased to 200°C, and the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3kPa or less for 30 minutes to obtain a polyester polyol (a2-1) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 0 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 100 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 2,000, the acid value was 0.5 mgKOH / g, and the hydroxyl value was 55 mgKOH / g.
[0047] (Synthesis Example 7) Polyester polyol (a2-2) 100 parts of adipic acid and 77 parts of 2-methyl-1,3-propanediol (MPO) were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.0 (mgKOH / g), the reaction temperature was increased to 200°C, and the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3kPa or less for 30 minutes to obtain a polyester polyol (a2-2) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 0 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 0 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 2,000, the acid value was 0.5 mgKOH / g, and the hydroxyl value was 55 mgKOH / g.
[0048] (Synthesis Example 8) Polyester polyol (a2-3) 100 parts of adipic acid and 65 parts of 1,2-propanediol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.0 (mgKOH / g), the reaction temperature was increased to 200°C, and the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3kPa or less for 30 minutes to obtain a polyester polyol (a2-3) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 0 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 0 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 2,000, the acid value was 0.5 mgKOH / g, and the hydroxyl value was 55 mgKOH / g.
[0049] (Synthesis Example 9) Polyester polyol (a2-4) 92 parts of adipic acid, 9 parts of isophthalic acid, and 90 parts of diethylene glycol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.0 (mgKOH / g), the reaction temperature was increased to 200°C, and the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3 kPa or less for 30 minutes to obtain a polyester polyol (a2-1) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 8 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 100 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 2,000, the acid value was 0.5 mgKOH / g, and the hydroxyl value was 55 mgKOH / g.
[0050] (Synthesis Example 10) Polyester polyol (a2-5) 100 parts of adipic acid, 69 parts of 2-methyl-1,3-propanediol, and 9 parts of diethylene glycol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.0 (mgKOH / g), the reaction temperature was increased to 200°C, and the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3 kPa or less for 30 minutes to obtain a polyester polyol (a2-5) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 0 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 10 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 2,000, the acid value was 0.3 mgKOH / g, and the hydroxyl value was 55 mgKOH / g.
[0051] (Synthesis Example 11) Polyester polyol (a3-1) 100 parts of isophthalic acid, 498 parts of adipic acid, 84 parts of ethylene glycol, and 423 parts of neopentyl glycol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.0 (mgKOH / g), the reaction temperature was increased to 200°C, the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3 kPa or less for 30 minutes, and then cooled to 110°C. Then, 5.5 parts of trimellitic anhydride was added and acid-modified at 110°C to obtain a polyester polyol (a3-1) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 15 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 0 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 750, the acid value was 3.6 mgKOH / g, and the hydroxyl value was 104 mgKOH / g.
[0052] (Synthesis Example 12) Polyester polyol (a3-2) 100 parts of isophthalic acid, 498 parts of adipic acid, 84 parts of ethylene glycol, and 423 parts of neopentyl glycol were charged into a reaction vessel, and the mixture was heated to 150-240°C while stirring under a nitrogen gas flow to carry out an esterification reaction. When the acid value reached 2.0 (mgKOH / g), the reaction temperature was increased to 200°C, and the pressure inside the reaction vessel was gradually reduced, and the mixture was reacted at 1.3 kPa or less for 30 minutes to obtain a polyester polyol (a3-2) in which the structural units derived from polybasic acids and monofunctional carboxylic acids having aromatic rings were 15 mol% based on the total amount of carboxyl group components, and the structural units derived from polyhydric alcohols having alkylene oxide groups were 0 mol% based on the total amount of hydroxyl group components. The number average molecular weight was 750, the acid value was 0.5 mgKOH / g, and the hydroxyl value was 107 mgKOH / g.
[0053] [Table 1]
[0054] <Adjustment of polyol base agent (A)> (Polyol base A-1 to A-14) The components were mixed according to the composition shown in Table 2 to prepare a polyol base.
[0055] [Table 2]
[0056] <Synthesis of polyisocyanate> (Synthesis Example 13) Aliphatic polyisocyanate (b-1) 75 parts of Takenate 500 (xylylene diisocyanate) and 200 parts of polyester polyol (a2-2) were charged into a reaction vessel, and the mixture was reacted at 110° C. for 4 hours while stirring under a nitrogen gas flow, to obtain an aliphatic polyisocyanate (b-1) having a urethane bond.
[0057] (Synthesis Example 14) Aliphatic polyisocyanate (b-2) 219.9 parts of HDI biuret (product name: Basonate HB-100, manufactured by BASF) and 30.1 parts of cyclohexanol were charged into a reaction vessel, and the mixture was reacted at 110°C for 4 hours while stirring under a nitrogen gas flow, to obtain an aliphatic polyisocyanate (b-2) having a urethane bond.
[0058] <Adjustment of polyisocyanate curing agent (B)> Polyisocyanate was mixed according to the composition shown in Table 3 to prepare a polyisocyanate curing agent.
[0059] [Table 3]
[0060] The abbreviations in Table 3 are as follows: HDI Biuret: Aliphatic polyisocyanate (product name: Basonate HB-100, manufactured by BASF) HDI Nurate: Aliphatic polyisocyanate (product name: Takenate D177N, manufactured by Mitsui Chemicals) IPDI Nurate: Aliphatic polyisocyanate (product name: VESTANAT T1890 / 100, manufactured by Evonik)
[0061] <Adjustment of solvent-free adhesive> [Adhesive 1-18] Adhesives 1 to 18 were prepared by mixing the polyol base agent (A) and the polyisocyanate curing agent (B) in the mass ratio shown in Table 4. The viscosity of each of the prepared adhesives at 40°C after 12 hours in an environment of 40°C was measured and is shown in Table 4.
[0062] [Table 4]
[0063] <Production of packaging materials> [Examples 1 to 14, Comparative Examples 1 to 3] A packaging material of transparent vapor-deposited PET (thickness 12 μm, GL-ARH (Toppan Printing Co., Ltd.)) / printing layer / adhesive layer / nylon (thickness 15 μm, Emblem ONBC (Unitika Ltd.), hereafter referred to as NY)) / adhesive layer / unstretched polypropylene (thickness 70 μm, Torayfan ZK207 (Toray Industries, Inc.), hereafter referred to as CPP) was prepared using the following method. First, a print layer with printed and unprinted areas was formed on a transparent vapor-deposited PET sheet using the gravure printing method with LP Bio white ink (manufactured by Toyo Ink Co., Ltd.). The thickness of the print area was 1 μm. After forming the printed layer, the solvent-free adhesive obtained above was applied to the printed layer using a nonsol laminator (SuperSimplex SL, manufactured by Nordmechanika) at a coating roll temperature of 70°C, a coating speed of 200 m / min, and a coating amount of 2.0 g / m 2 The coated surface was then bonded to the NY. Next, the same solvent-free adhesive as above was applied to the NY side of the laminated transparent vapor-deposited PET / NY using a nonsol laminator at a coating roll temperature of 70°C, a coating speed of 200 m / min, and a coating amount of 2.0 g / m. 2 The coated surface was then bonded to the CPP. Next, the obtained laminate was aged in an environment of 40° C. for 72 hours to obtain a packaging material.
[0064] <Evaluation of packaging materials> The appearance and retort resistance of the obtained packaging material were evaluated by the following methods. The evaluation results are shown in Table 5.
[0065] [Appearance evaluation] The printed and plain parts of the obtained packaging material were each photographed from the CPP surface at a magnification of 50x using a microscope (product name "VHX-6000": manufactured by Keyence Corporation). The images obtained were then subjected to a binarization process, and the area ratio of the air bubble part to the total area of the observed image was measured as a result of quantitative observation, and classified according to the following criteria. A: Air bubble area ratio is less than 0.5% (very good) B: Air bubble area ratio is 0.5% or more and less than 1.0% (good) C: Bubble area ratio is 1.0% or more and less than 2.0% (fairly good) D: Air bubble area ratio is 2.0% or more and less than 3.0% (practical lower limit) E: Air bubble area ratio is 3.0% or more (not suitable for use)
[0066] [Retort resistance] The obtained package was heat-sealed at 190°C for 1 second with the CPP facing inward to produce a bag measuring 14cm x 18cm. The heat-seal width was 15mm. The contents were filled with a mixture of 3% acetic acid aqueous solution / ketchup / salad oil in a mass ratio of 1 / 1 / 1. The bag was sterilized with hot water at 30 rpm, 135°C, and 30 minutes under pressure using a rotary retort tester, and then the heat-sealed portion of the bag was cut to a width of 15mm and pulled at a peel speed of 300mm / min in an environment of 25°C and 50% relative humidity to measure the heat-seal strength. A: Heat seal strength is 50N or more (very good) B: Heat seal strength is 40N or more and less than 50N (good) C: Heat seal strength is 30N or more and less than 40N (fairly good) D: Heat seal strength is 20N or more and less than 30N (practical lower limit) E: Heat seal strength is less than 20N (not suitable for use)
[0067] [Table 5]
[0068] As shown in this example, it was found that the packaging material according to the present disclosure is a packaging material that combines high appearance and high retort performance.
Claims
1. A packaging material for heat-sterilized food, comprising: At least a transparent deposition film layer, an adhesive layer, and a plastic film layer are provided in this order; The adhesive layer is a cured product of a solventless adhesive, The solventless adhesive comprises a polyol base agent (A) containing a polyester polyol and a polyisocyanate curing agent (B) containing an aliphatic polyisocyanate, and after mixing the polyol base agent (A) and the polyisocyanate curing agent (B), the viscosity at 40°C after 12 hours at 40°C is 80 Pa·s or less. packaging material.
2. The polyol base (A) contains a first polyester polyol (a1), The first polyester polyol (a1) has structural units derived from a polybasic acid having an aromatic ring and / or a monofunctional carboxylic acid having an aromatic ring, and contains the structural units in a total amount of 20 mol % or more based on the total amount of carboxy group components. The packaging material according to claim 1.
3. The first polyester polyol (a1) contains 0 to 30 mol % of a structural unit derived from a polyhydric alcohol having an alkylene oxide group based on the total amount of hydroxyl group components. The packaging material according to claim 2.
4. The polyol base (A) further contains a second polyester polyol (a2), The second polyester polyol (a2) has structural units derived from a polybasic acid having an aromatic ring and / or a monofunctional carboxylic acid having an aromatic ring, and contains the structural units in a total amount of 10 mol % or less based on the total amount of carboxy group components. The packaging material according to claim 2 or 3.
5. The second polyester polyol (a2) contains 0 to 20 mol % of a structural unit derived from a polyhydric alcohol having an alkylene oxide group based on the total amount of hydroxyl group components. The packaging material according to claim 4.
6. The packaging material of claim 1 , wherein the solvent-free adhesive comprises an inorganic filler.
Citation Information
Patent Citations
Two-part curable solventless adhesive
JP2006213801A
Adhesive composition and laminate
JP2016121351A
Solventless type adhesive, laminate film and package using the same
JP2018197310A
Laminate film, packaging bag, method for producing laminate film, and method for producing packaging bag
JP2021066031A
Two-component adhesive composition and method of manufacturing same
JP2022008540A